TRICHODESMA KUMAREUM (BORAGINACEAE), A NEW SPECIES FROM NORTH EAST INDIA - Sanatombi Devi YumkhamSanatombi Devi Yumkham; Naorem Premita Devi; Sandhyarani Devi Khomdram; Mayanglambam Roma Devi (Reinwardtia, 2019)
YUMKHAM, S. D., DEVI, N. P., KHOMDRAM, S. D. & DEVI, M. R. 2 019. Trichodesma kumareum (Boraginaceae), a new species from North East India. Reinwardtia 18(2): 105−113. — A new species, Trichodesma kumareum S.D.Yumkham, N.P.Devi, S.D.Khomdram & M.R.Devi (Boraginaceae) is described and illustrated from Manipur State of North East India. It shows affinity with T. khasianum and T. calycosum, but can be differentiated from the rest by its larger size in habit, helicoid cyme, closely packed numerous flowers ranging between 120–160 in number per inflorescence, presence of eight faucal appendages at the base of corolla lobes, adpressed urn–shaped flowering calyx and 1–4 lobed ovaries. A comprehensive description, photographs, relevant notes, conservation status and key to species are incorporated.